Prediction role of a novel biomarker ST2 in risk assessment of adverse cardiovascular events in chronic heart failure with preserved and intermediate ejection fraction after myocardial revascularization - E. V. Grakova; A. T. Teplyakov; K. V. Kopieva; Sh. D. Akhmedov; O. N. Ogurkova; M. V. Soldatenko (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate prediction role of the biomarkers soluble ST2 (sST2) and natriuretic hormone N-terminal propeptide (NT-proBNP) in risk assessment of adverse cardiovascular events (ACVE) in coronary heart disease patients (CHD) with chronic heart failure (CHF) after myocardial revascularization.Material and methods. Totally, 87 patients included (72 males) with CHD and CHF I-III functional class by NYHA with ejection fraction of the left ventricle (LVEF) 63 [55; 65]%, mean age 63 [57; 69] y.o. Levels of sST2 and NT-proBNP in plasma were measured by immune enzyme assay before myocardial revascularization.Results. In 12 months of prospective follow-up, patients were selected to 2 groups according to clinical course of CHF. To the group I the patients included (n=35) with ACVE, group II (b=52) — with none. It was found that in the group I the level of sST2 was higher by 41,5% (p<0,001) and reached 46,78 [37,88; 64,96] ng/mL, and in the group II — 27,39 [23,02; 35,4] ng/mL. Concentration of NT-proBNP in the group with ACVE was 2,5 times (p=0,004) higher comparing with group II and reached 189,21 [74,46; 580,79] and 73,58 [26,64; 155,77] pg/mL, respectively. In ROC-analysis it was found that the level of sST2  ≥34,18 ng/mL (sensitivity — 90,6%, specificity — 75,0%, AUC — 0,88, р<0,0001) and level of NT-proBNP  ≥276,96 pg/mL (sensitivity — 88,4%, specificity — 43,7%, AUC — 0,64, р<0,004) can be regarded as markers of ACVE during 12 months in CHD and CHF patients after revascularization. Also, together these two markers increase predictive significance of the analysis (sensitivity — 92,6%, specificity — 77,1%, AUC — 0,90, р<0,0001).Conclusion. Therefore, the preprocedural level of sST2 can be regarded as non-invasive marker for prediction of ACVE. Combination of sST2 and NT-proBNP shows higher diagnostic sensitvity and specificity for prediction of adverse CHF course.